Penyuluhan Kepada Orang Tua Tentang Membangun Karakter Resiliens Pada Anak Sejak Dini - Zunaidah, Farida Nurlaila; Kurnia, Ita; Aka, Kukuh Andri; Basori, Muhamad (Universitas Nusantara PGRI Kediri, 2021)
Counseling to parents about building resilient character in elementary school children. An outreach activity that aims to provide information to parents on the importance of building resilient character in children. Resilience character is a child's ability to adapt to all environmental conditions. Resilient character needs to be built from an early age so that children have a strong mentality and do not give up easily. This extension activity uses a survey method using a questionnaire before the extension begins and after the extension is carried out. A survey questionnaire to find out the understanding of parents' guardians about the character of resilience before being given counseling and understanding of parents after counseling and the benefits of participating in the counseling. The results of the counseling show that of the 30 parents of parents who took part in the counseling, they did not understand what resilient character was. After counseling, all parents understand the character of resilience, express the benefits of resilience and various opinions in fostering resilient character in their children.